2006
DOI: 10.1177/0093854805284406
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Prison Misconducts

Abstract: A meta-analysis was conducted to assess the effectiveness of correctional treatment for reducing institutional misconducts. Sixty-eight studies generated 104 effect sizes involving 21,467 offenders. Behavioral treatment programs produced the strongest effects ( r = .26, CI = .18to .34). The numbers of criminogenic needs targeted and program therapeutic integrity were found to be important moderators of effect size. Prison programs producing the greatest reductions in misconduct were also associated with larger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
120
1
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(127 citation statements)
references
References 78 publications
4
120
1
2
Order By: Relevance
“…Waters and Megathlin (2002) found significant improvements in inmate perceptions of a prison social climate 22 months after rehabilitation workers were employed. Similarly, a meta-analysis of 68 studies assessing the effectiveness of correctional treatment revealed that settings that provided behavioural treatment programs delivered by professional staff experienced the lowest rates of prison misconduct (French & Gendreau 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Waters and Megathlin (2002) found significant improvements in inmate perceptions of a prison social climate 22 months after rehabilitation workers were employed. Similarly, a meta-analysis of 68 studies assessing the effectiveness of correctional treatment revealed that settings that provided behavioural treatment programs delivered by professional staff experienced the lowest rates of prison misconduct (French & Gendreau 2006).…”
Section: Discussionmentioning
confidence: 99%
“…La aplicación de las EA en ambientes penitenciarios se realiza sobre la base de considerar, al menos, la prisión como un suceso traumático para una persona (S. D. Phillips, 2010;Rodríguez Díaz, Álvarez Fresno, García Zapico, Longoria, & Noriega Carro, 2013;Rodríguez Díaz et al, 2011), que impacta y genera una cadena de estresores -difi cultades de pareja, disminución de ingresos, comunicación con los seres queridos (hijos, padres, pareja, …), alejamiento familiar, drogodependencia, … (Degobbi & Rezende, 2011;Mikulic & Crespi, 2004;Moreno & Mellizo, 2006), así como límites para manejar difi cultades y generar cambios en la conducta (French & Gendreau, 2006) y pensamientos (Giordano, Cernkovick, & Rudolph, 2002), así como para mantenerlas estables a lo largo de la intervención con el interno para adaptarse a diferentes contextos (Blevins, Johnson, Cullen, & Lero, 2010;Johnson, Colvin, Hanley, & Flannery, 2010), dando lugar a nuevas pautas comportamentales, de roles y modalidades relacionales como forma de adaptarse a sus demandas y requerimientos (Pereira, Scheffer, & Martins de Almeida, 2012;Rodríguez Díaz, Álvarez Fresno, García Zapico, Longoria, & Noriega Carro, en prensa). Es decir, las EA son básicas a la hora de lograr construir una nueva historia de vida para el individuo que necesita de una nueva oportunidad, si cabe todavía más para aquellos que se refi eren en el ámbito de la inadaptación social.…”
Section: Y Agencia Española De Cooperaciónunclassified
“…Biased cognitions are also thought to contribute to the occurrence of aggression and, as a result, numerous cognitive -behavioural interventions have been developed (see Bush 1995 ;McGuire 2002 ;Dodge 2003 ;Edgar et al 2003 ;French and Gendreau 2006 ). Yet, recent research has failed to fi nd a relationship between these cognitive biases and involvement in confrontations between prisoners (see Butler 2007 ).…”
Section: Defending the Selfmentioning
confidence: 99%
“…Currently, cognitive -behavioural interventions tend to be frequently used to reduce aggressive behaviour ( Bush 1995 ;McGuire 2002 ;French and Gendreau 2006 ). However, there are concerns about their pathologizing nature, limited ability to address the social causes of behaviour and their failure to grasp how men's use of violence relates to their view of themselves and their masculinity ( Merrington and Stanley 2000 ;Kendall 2002 ;Gadd 2004 ;Maruna and Mann 2006).…”
Section: Reducing Aggression In Prisonmentioning
confidence: 99%